2017
DOI: 10.1016/j.ydbio.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the unique torpor of Botrylloides leachi, a colonial urochordate

Abstract: Rough environmental conditions make the survival of many multi-cellular organisms almost impossible, enforcing behavioral, morphological, physiological and reproductive rejoinders that can cope with harsh times and hostile environments, frequently through down-regulation of metabolism into basal states of dormancy, or torpor. This study examines one of the most unique torpor strategies seen within the phylum Chordata, exhibited by the colonial urochordate Botrylloides leachi, which enters a state of hibernatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…We repeatedly observed that colonies isolated in smaller tanks will present signs of stress and enter into hibernation within a few days, as observed following environmental stresses like low temperatures (Hyams et al, 2017). Based on the communicated crucial role of inoculating artificial seawater with a suitable microbiota (Oliveri, personal communication, unpublished), we decided to investigate the role of bacteria for the survival of Botrylloides in ASW.…”
Section: A Suitable Marine Microbiota Is Necessary To the Survival Of B Diegensismentioning
confidence: 99%
“…We repeatedly observed that colonies isolated in smaller tanks will present signs of stress and enter into hibernation within a few days, as observed following environmental stresses like low temperatures (Hyams et al, 2017). Based on the communicated crucial role of inoculating artificial seawater with a suitable microbiota (Oliveri, personal communication, unpublished), we decided to investigate the role of bacteria for the survival of Botrylloides in ASW.…”
Section: A Suitable Marine Microbiota Is Necessary To the Survival Of B Diegensismentioning
confidence: 99%
“…This system is essential during tissue repair, as it transports factors and cells required for regeneration (Brown et al, 2009a. Additionally, in case of adverse climatic conditions, colonies enter a dormancy stage through the resorption of all zooids, leaving only blood vessels (Hyams et al, 2017). The blood vessel system in Symplegma + Botryllids colonies maintains physiological cohesion and allows communication between zooids.…”
Section: Evolution Of Coloniality In the Symplegma + Botryllids Cladementioning
confidence: 99%
“…Blood vessels systems maintain cohesion and homeostasis of the colony. Vessels have the capacity to rearrange in case of external disturbance (Gutierrez & Brown, 2017) ; or by the dormancy at cold season, by the resorption of all zooids maintaining only the blood vessel system (Hyams et., 2017). The plasticity of the blood vessels system is decisive in the capacity of self-organization of the colonies.…”
Section: Modularity Of a Multicellular Individual By The Development mentioning
confidence: 99%